2021
DOI: 10.1371/journal.pone.0251984
|View full text |Cite
|
Sign up to set email alerts
|

Which personality traits can mitigate the impact of the pandemic? Assessment of the relationship between personality traits and traumatic events in the COVID-19 pandemic as mediated by defense mechanisms

Abstract: The COVID-19 pandemic has had a significant influence on the lives of people around the world and could be a risk factor for mental health diseases. This study aimed to explore the psychological impact of the COVID-19 pandemic by identifying patterns related to post-traumatic symptoms by considering personality and defensive styles. Specifically, it was hypothesized that neuroticism was negatively associated with impact of event, as opposed to extraversion, agreeableness, conscientiousness, and openness traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
34
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 70 publications
11
34
1
2
Order By: Relevance
“…With regard to defence mechanisms, from the implemented models it emerges that anxiety was negatively associated with the use of mature styles which was in turn related to lower stress, as opposed to neurotic or immature ones. This is in line with previous studies conducted during the lockdown which highlighted the association between mature and neurotic mechanisms with posttraumatic symptoms (Gori et al, 2021 ) and the negative association between mature defences with psychological symptoms (Di Giuseppe et al, 2020 ; Gori et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With regard to defence mechanisms, from the implemented models it emerges that anxiety was negatively associated with the use of mature styles which was in turn related to lower stress, as opposed to neurotic or immature ones. This is in line with previous studies conducted during the lockdown which highlighted the association between mature and neurotic mechanisms with posttraumatic symptoms (Gori et al, 2021 ) and the negative association between mature defences with psychological symptoms (Di Giuseppe et al, 2020 ; Gori et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, an integration of our results with existing evidence can provide a useful contribution for more effective management of the emergency and its psychological consequences, as well as physical ones. For example, previous studies highlighted individual differences concerning the use of mature, neurotic, immature defences and their contribution in determining the impact of events during the COVID‐19 lockdown (Gori et al, 2021 ), while others have emphasized the protective effect of life satisfaction in comparisons of perceived stress (Gori et al, 2020 ). In other words, these and other research identify risk or protective factors regarding some variables considered in this study, which therefore adds a further piece in this field and can be useful for future research and to provide further knowledge of the psychological consequences of restrictive measures related to COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Restrictions to contain the virus, economic instability, risk of contagion, uncertainty about the future, unpredictability of the virus spread, and the growing emergence of its variants may cause significant and lasting effects on mental health [ 6 ]. Some cross-sectional studies have already shown the emotional impact of the lockdown and the early stages of the pandemic, highlighting high levels of distress [ 7 , 8 ], post-traumatic symptoms [ 7 , 9 ], worry [ 10 , 11 ], and anxiety [ 7 , 11 ], underlining the strong link between compliance with restrictions and moral disengagement [ 12 ], and noting the differences in the effects on mental health according to gender [ 13 , 14 ]. One year after the outbreak, with the in-place vaccination campaign, maintenance of preventive measures, and alternation of localized closure phases, it could be important to monitor the progress of the psychological effects of the health emergency in order to promote adequate and targeted implementation of supportive and therapeutic interventions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding vulnerability and protective factors of psychological distress, a growing number of studies have found that a person's individual characteristics, such as personality traits, may account for some of the variances in people's (including HCWs') reactions to the pandemic [35][36][37][38], which is consistent with findings from pre-pandemic studies [39,40]. Although there is sufficient research on the relationship between personality traits and mental health, the relationship between personality traits and both attachment style and metacognitive functioning during the COVID-19 pandemic is still under-developed and usually focused on the general population rather than HCWs specifically.…”
Section: Introductionmentioning
confidence: 99%